APPLICATION OF THE AHP METHOD IN DETERMINING OUTSTANDING STUDENT BASED ON INDICATORS OF EDUCATION AND STUDENT ACTIVITIES AT FTI UKSW - Munda', Mourin; J. P, Sri Yulianto (Jurnal Teknik Informatika (Jutif), 2023)
The decision making system is a computer-based system that aims to assist in the decision-making process by using existing data to solve semi-structured problems. This research aims to develop an efficient and objective approach for selecting outstanding students in the higher education environment of FTI UKSW. Until now, FTI UKSW has been using manual methods to determine outstanding student. The Analytical Hierarchy Process methods is employed as the primary framework in this research to measure and analyze relevant criteria and sub-criteria for the selection of outstanding student. In assessing outstanding students, several criteria are required, including Cumulative Grade Point Average, Academic Research, Skills/Achievements, English Proficiency, and Extracurricular Activities. The determination of outstanding student using the Analytical Hierarchy Process methods is designed in the form of a web application to simplify the decision-making process for the faculty. The results of the Analytical Hierarchy Process analysis produce relative priorities for each student based on educational indicators and extracurricular activities. Thus, this research provides a systematic framework for decision making in selecting outstanding students that is more objective.